(untitled) (KMC Journal, 2023)
The article explores how Nepalese public schools’ traditional hierarchy-dominated educational culture shapes teachers’ professional growth and sense of identity. Through the narrative inquiry approach, I explored teachers’ professional identity development using Gee’s (2000) identity framework. The data revealed that hierarchy and power relations between the teachers and the social context fundamentally shaped teacher identity development. However, the study further showed that professional hierarchy was not uni-layered, the power was not one-directional, and the domination was not permanent but rather dynamic. Factors like academic qualifications, job status, technological skills, and social status made the hierarchy complex. More interestingly, hierarchical relationships did not always undermine teacher empowerment but confidence in some cases. For example, when a teacher in a marginalized position due to some factors such as poor health condition was viewed as a role model or capable of success despite challenges, they achieved high value from their colleagues.